Selenium and potassium supplementation improve nitrogen metabolism, antioxidant activity, and osmolyte production, reducing the growth and photosynthetic inhibition caused by polyethylene glycol (PEG) in wheat - Ayshah Aysh ALRASHIDI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Drought stress has a significant impact on all crops, affecting both their growth and development. In this study, wheat plants were subjected to drought stress induced by 15% of PEG along with or without supplementation of selenium and potassium supplements. Plants subjected to PEG alone showed a decrease in a number of plants morphophysiological and biochemical parameters such as a decline in plant height, dry mass, carotenoids, total chlorophyll, stomatal conductance, net photosynthesis, and intercellular CO2 levels. Nevertheless, adding selenium and potassium supplements effectively mitigated these decreases. PEG's drought also led to the overproduction of harmful ROS-inducing substances, H2O2 and O2. Certain factors led to a significant instance of lipid peroxidation, which the addition of selenium and potassium effectively reduced and leaded to protection of plants from oxidative stress damage. The combination of selenium and potassium also significantly reduced the protease and lipoxygenase activities. This effect was even more noticeable when dealing with synergic Se+K applications. The levels of enzymatic (CAT, SOD, APX, and GR) and non-enzymatic (AsA, GSH, and tocopherol) antioxidants went up a lot after treatment with PEG. Moreover, the inclusion of selenium and potassium supplements further amplified the increase. Adding selenium and potassium supplements improved the activity of nitrate reductase (NR), an enzyme that breaks down nitrogen. The combination treatment has shown remarkable efficacy in reducing the adverse effects caused by PEG. Furthermore, the research revealed that the inclusion of selenium and potassium supplements led to heightened quantities of phenols and flavonoids. As a result of the drought, there was a limited absorption of mineral ions, such as nitrogen, phosphorus, potassium, and calcium. However, the addition of selenium and potassium supplements significantly mitigated this decline.